FAKTOR-FAKTOR YANG MEMPENGARUHI FIRM VALUE PADA PERUSAHAAN SEKTOR KONSUMEN PRIMER - Verren Lee; Sufiyati Sufiyati (Fakultas Ekonomi, Universitas Tarumanagara, 2026)
The purpose of this research is to obtain empirical evidence about the effects of profitability, firm size, firm growth and liquidity on firm value which is proxied by tobin’s q in consumer non-cylicals sector companies that listed on the Indonesia Stock Exchange (IDX) for 2019-2021 period. This research used 37 primary consumer sector companies with a total of 111 data from the consumer non-cylicals sector companies and the used purposive sampling method. Data processing was processed by multiple regression analysis and used secondary data through the IDX website then inputted and processed using the SPSS software program version 25. The results of this study showed that profitability has significant negative effect on firm value, firm size, firm growth and liquidity have no significant effect on firm value. The implication of this study is the important of the firm value that can influence a positive signal to investors.